PERANAN MAHKAMAH KONSTITUSI DALAM MEMPERKUAT KOMISI PEMBERANTASAN KORUPSI - Taryana, Usep; Husodo, Jadmiko Anom (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This legal research aims to find out about the role of the Constitutional Court in strengthening the Corruption Eradication Commission which is reviewed from the implementation of its authority to examine constitutional review. This study is a normative legal research using secondary data in the form of primary legal materials and secondary legal materials. The data was collected by library research and using a model of legislation and conceptual approach. Research results show that there are attempts to weaken the KPK, including by submitting applications for testing the KPK Act. to the Constitutional Court. However, based on the analysis of the decision from 2003-2017, it was known that the Constitutional Court had actually played a role in strengthening the KPK in terms of its authority and institutions.